Minimization of the thermal state of the hub of a friction pair. Issue 4 (3rd April 2018) - Mirsalimov, Vagif M.; Akhundova, Parvana E.
ABSTRACT: Theoretical analysis for defining the function of displacements of a hub's external contour points and the microgeometry of the friction surface, ensuring minimization of the thermal state of the hub of a friction pair, is performed based on the model of rough friction surfaces and minimax criterion. A closed system of algebraic equations is constructed, allowing the solution to the problem of the optimal design of the friction pair to be obtained, depending on geometric and thermophysical characteristics of the hub and plunger. The resulting functions of displacements of the hub's external contour points and microgeometry of the friction surface ensure the increased serviceability of the friction pair.